2022
DOI: 10.1177/14713012221077533
|View full text |Cite
|
Sign up to set email alerts
|

Practice of end-of-life care for patients with advanced dementia by hospital physicians and nurses: Comparison between medical and surgical wards

Abstract: Background Patients with advanced dementia are commonly hospitalized in acute care wards, yet there is limited data regarding the end-of-life (EOL) care delivered to this population. The aim of the study was to examine EOL care delivered to patients with advanced dementia hospitalized on acute wards as reported by physicians and nurses. Methods Participants were physicians and nurses from medical and surgical wards of two tertiary hospitals in Israel. Participants completed a self-report questionnaire evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Indeed, the lack of acquaintance regarding the options for end-of-life care was found to be a barrier to effective discussions about end-of-life among internal medicine residents [ 52 ]. We have recently reported that health personnel in general hospitals report low rates of end of life discussions with family members of hospitalized patients with dementia [ 53 ]. Some investigators found that knowledge deficits were negatively correlated with perceived self-efficacy [ 54 , 55 ], and positively correlated with lack of confidence in making care decisions for patients with AD and concerns about their ability to provide quality end-of-life care [ 12 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the lack of acquaintance regarding the options for end-of-life care was found to be a barrier to effective discussions about end-of-life among internal medicine residents [ 52 ]. We have recently reported that health personnel in general hospitals report low rates of end of life discussions with family members of hospitalized patients with dementia [ 53 ]. Some investigators found that knowledge deficits were negatively correlated with perceived self-efficacy [ 54 , 55 ], and positively correlated with lack of confidence in making care decisions for patients with AD and concerns about their ability to provide quality end-of-life care [ 12 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha Cronbach values of the MSQ and the PMCS in this study were 0.87 and 0.93, respectively, similar to the previous reports among nurses in the literature ( 53–56 ) (see Supplemental Files 1a and 1b for the Hebrew version of the MSQ and PMCS tools, respectively). (4) The authors designed the fourth questionnaire to evaluate the treatment approach for persons with AD in emergency life-threatening situations ( 6 , 31 ). The treatment approach was measured by analyzing responses to a hypothetical scenario of a person with AD presenting with aspiration pneumonia and acute respiratory failure in an acute care hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The sum of the scores of the chosen interventions was termed the “Treatment Approach Score” and ranged from −1 to 11 (see Supplemental file 2a for the Questionnaire and Supplemental file 2b for the Hebrew Version of this Questionnaire). The authors designed this questionnaire and reviewed it for content validity using a panel of six geriatricians working in acute care settings ( 6 ). The fifth questionnaire included 12 items that assess potential components related to the following three cognitive biases: representativeness, availability, and anchoring.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations